2005
DOI: 10.1098/rstb.2005.1766
|View full text |Cite
|
Sign up to set email alerts
|

The role of an astrocytic NADPH oxidase in the neurotoxicity of amyloid beta peptides

Abstract: Amyloid beta peptide (Ab) accumulates in the CNS in Alzheimer's disease. Both the full peptide (1-42) or the 25-35 fragment are toxic to neurons in culture. We have used fluorescence imaging technology to explore the mechanism of neurotoxicity in mixed asytrocyte/neuronal cultures prepared from rat or mouse cortex or hippocampus, and have found that Ab acts preferentially on astrocytes but causes neuronal death. Ab causes sporadic transient increases in [Ca 2C ] c in astrocytes, associated with a calcium depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 26 publications
3
129
0
Order By: Relevance
“…Functional subunits of NADPH oxidase have been detected in the neurons of various regions of the mouse brain, including hippocampus, cortex, amygdala, striatum, and thalamus (Serrano et al, 2003;TejadaSimon et al, 2005). Astrocytic NADPH oxidase has been implicated in the neurotoxicity of amyloid beta peptides (Abramov and Duchen, 2005). MZ may interact with nonphagocytic NADPH oxidase generating ROS independent of microglia involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Functional subunits of NADPH oxidase have been detected in the neurons of various regions of the mouse brain, including hippocampus, cortex, amygdala, striatum, and thalamus (Serrano et al, 2003;TejadaSimon et al, 2005). Astrocytic NADPH oxidase has been implicated in the neurotoxicity of amyloid beta peptides (Abramov and Duchen, 2005). MZ may interact with nonphagocytic NADPH oxidase generating ROS independent of microglia involvement.…”
Section: Discussionmentioning
confidence: 99%
“…PT in astrocytes is an important step toward cell death caused by ␤A (20). For hippocampal astrocytes expressing MGP, the proportion of dead cells decreased from 23.7 Ϯ 2.2% to 12.6 Ϯ 1%; P Ͻ 0.001, and, for neurons, it decreased from 51.9 Ϯ 4.6% to 17.9 Ϯ 1.4%, P Ͻ 0.001.…”
Section: Pt-dependent Cell Death and Polyp Ppx Expression Protects Amentioning
confidence: 95%
“…In our ␤A experiments, polyP depletion protected both neurons and astrocytes. We have demonstrated that ␤A acts directly on astrocytes, inducing increases in cytoplasmic Ca 2ϩ and consequent PT, whereas neuronal cell death is caused by oxidative stress transmitted from astrocytes (20).…”
Section: Involvement Of Polyp In Regulation Of Normal Mitochondrial Fmentioning
confidence: 99%
“…Oxidative damage could be detected prior to observation of plaques in both human and in animal models, pointing to inflammation as an early event in AD [166,167]. The major source of oxidants is generally thought to be the microglial and/or astrocyte Nox2-type system [166,[168][169][170], although there is also increased expression of Nox1 and Nox3 in AD brain [164].…”
Section: B Nox Enzymes and Alzheimer's Diseasementioning
confidence: 99%